Seroprevalence and risk factors associated with visceral leishmaniasis in dogs in Jaciara, State of Mato Grosso - Priscila Marcidelli Lopes; Eveline da Cruz Boa Sorte; Naiani Domingos Gasparetto; Cenita Maria Oliveira; Arleana do Bom Parto Ferreira de Almeida; Valéria Régia Franco Sousa (Revista da Sociedade Brasileira de Medicina Tropical, 2014)
Introduction Visceral leishmaniasis is a neglected disease. Jaciara, State of Mato Grosso has the most cases. This study aimed to determine the risk factors and seroprevalence of canine visceral leishmaniasis in urban and rural areas. Methods This cross-sectional study of domestic dogs used enzyme-linked immunosorbent assay and indirect immunofluorescence test. Results The prevalence was 54.7% among 345 analyzed samples. Short coat, age of 1-6 years, and living less than 100m from vegetation posed the highest infection risks. Conclusions Certain dog behaviors and characteristics, and their correlation with environmental conditions, were relevant in the high prevalence of canine leishmaniasis in Jaciara.